Enhancing Students’ Reading Comprehension with Gamification of Local Wisdom Stories during Emergency Online Learning - Nitiasih, Putu Kerti; Permana, I Gede Yoga; Budiartha , Luh Gd Rahayu (Universitas Pendidikan Ganesha, 2022)
During online learning time, students are required to learn more independently. However, the absence of learning media to support learning process makes it difficult for students to understand the learning material. This current study was aimed at analyses the impact of gamification of local wisdom stories towards students’ reading comprehension during emergency remote teaching. The study was an experimental study with pretest posttest design followed by 127 students in two selected primary schools. In conducting the study, students were given pretest about their reading comprehension, introduced and taught with gamification of local wisdom stories, and given posttest after finishing the material available in gamification. The instruments used have been through expert tests and field tests. Descriptive analysis was conducted to find the mean score and standard deviation. From the results of descriptive and inferential analysis, it was found that the mean score students’ reading comprehension in posttest (80.27) was higher than the pretest (72.91). A significant mean difference was identified based on the result of paired sample t test (Sig. 2-tailed= .001). The study concludes that the use of gamification of local wisdom stories was able to enhance students’ reading comprehension. Suggestions for further study are also encouraged in order to enhance the quality of gamification and students’ learning satisfaction.